PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP MOTIVASI SEBAGAI INTERVENING YANG BERDAMPAK PADA KINERJA KARYAWAN PADA PERUSAHAAN MANUFACTURE DI KAWASAN KARAWANG INTERNATIONAL INDUSTRY CITY (KIIC) - Fauzan, Akhmad; Putriana, Lies; Miranda , Agustinus (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2022)
The purpose of this study was to determine the effect of leadership style and organizational culture on motivation as an intervening impact on the performance of employees in the Manufacture company in the Karawang International Industry City (K II C) (case of the case in the company PT. Dai-chi Kimia Raya). The sample in this study was 185 employees. Data analysis methods use sem-pls with SmartPLS 3.0 applications. The results showed that organizational culture had a positive but not significant effect on employee motivation at PT. Dai-chi Kimia Raya. In the leadership style variable it is known to have an influence on employee motivation. Organizational culture directly affects employee performance of 0.134 or (13.4%) while leadership style variables have a significant effect directly on employee performance of 0.512 or (51.2%). In the working motivation variable on employee performance obtained a coefficient value of 0.463 or (46.3%). This can be concluded that the leadership style has a significant influence directly greater than organizational culture on employee performance. On indirect influence, organizational cultural variables have indirect influence on employee performance through work motivation by 0.042 or (4.2%) while the leadership style variable has indirect influence on employee performance through work motivation of 0.096 or (9.6 %). It can be concluded that leadership styles have indirect influence greater than organizational culture on employee performance through work motivation. The value of R Square for the working motivation variable obtained is 0.053 or 5.3%. The value of R Square for the employee performance variable obtained is 0.618 or 61.8%. These results show that leadership style, organizational culture and work motivation together have an effect of 61.8% of employee performance.